Factors that modulate the intergenerational transmission of autobiographical memory from older to younger generations. Issue 2 (7th February 2020) - Gu, Xuan; Tse, Chi-Shing; Brown, Norman R.
ABSTRACT: The present study examined the intergenerational factors in transmitting autobiographical memories from one generation to the next. Older adults from Beijing, China reported a collection of personally important autobiographical memories and their middle-aged children recalled important parental memories. The parent-child dyads independently recalled and provided ratings of mnemonic characteristics for the memories. Across generations, consensus memories, which refer to the memories that both parents and children considered as important in the parent's life, were characterised by the substantial material change that the events brought about in their lives. While parent-child interaction affected the number of events passed onto children, it only affected the number of script-divergent events that were not recorded in the life script of a culture, but not the number of script-consistent events. In addition, children whose parents were rusticated and relocated to rural areas during the Cultural Revolution remembered more historical memories than children whose parents were not rusticated. The findings shed light on the process that one generation gains the biographical knowledge and historical experience of a prior generation. Theoretical implications are discussed.